2022
DOI: 10.1177/23814683221097064
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening within Colonoscopy Capacity Constraints: Can FIT-Based Programs Save More Lives by Trading off More Sensitive Test Cutoffs against Longer Screening Intervals?

Abstract: Introduction. Colorectal cancer (CRC) prevention programs using fecal immunochemical testing (FIT) in screening rely on colonoscopy for secondary and surveillance testing. Colonoscopy capacity is an important constraint. Some European programs lack sufficient capacity to provide optimal screening intensity regarding age ranges, intervals, and FIT cutoffs. It is currently unclear how to optimize programs within colonoscopy capacity constraints. Design. Microsimulation modeling, using the MISCAN-Colon model, was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We assessed the full texts of the remaining 56 studies and 7 additional studies identified from manual reference checking. A total of 39 studies were ultimately included [ 6 , 17 , 18 , 20 56 ]. A PRISMA diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed the full texts of the remaining 56 studies and 7 additional studies identified from manual reference checking. A total of 39 studies were ultimately included [ 6 , 17 , 18 , 20 56 ]. A PRISMA diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Programmes have typically used gFOBT or FIT as the primary screening test and then employ colonoscopy to triage primary screen positives. FIT has superior test sensitivity to gFOBT and the advantage of the ability to quantitatively adjust the sensitivity and specificity trade-off by varying the FIT cut-off threshold for test positivity [ 6 ]. Thus, many programmes have switched from gFOBT to FIT [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRC screening is subject to the World Health Organization (WHO) principles of screening, as first discussed by Wilson and Jungner [ 8 ], whereby understanding the interplay of the harms and benefits of the ability to test for the pre-clinical disease is a necessary step in health planning. Decision-makers need to consider the most cost-effective approach for their service in order to best understand whether a non-invasive diagnostic test, such as FIT, at a particular threshold, is cost-effective within a limited capacity [ 9 ]. Crucially, these screening principles have led to the application of cost-effectiveness analyses to evaluate screening and support decision-makers in their planning and delivery of services.…”
Section: Introductionmentioning
confidence: 99%